Emergência da identidade profissional na formação inicial de professores de inglês: um estudo sob o viés da teoria da complexidade - GAIGNOUX, Kelly Cristina Marques (Universidade Federal do Pará, 2022)
The process of becoming a teacher of an additional language reveals different faces. In the contemporary world, it is a challenge to foster reflective and critical professionals who can question themselves as social and professional individuals, the ones that are always problematizing reality to take a stand politically, culturally, and economically in the contexts they work. Thus, this research proposes as a general objective to comprehend the development of the professional identity in English Language undergraduate students from the campus of the Federal University of Pará in Bragança (PA), during the last four academic semesters, from the perspective of Complexity Theory. To substantiate our discussion on the notions of subject and identity, we sought support in the studies of Bakhtin (2006 [1929]), Bauman (2005), Block (2007), Giddens (2002), Hall (2006), Moita Lopes (2002), and Resende (2009). In the field of professional identity, we concentrated on the writings of Tardif (2014 [2002]), Pimenta (2010), and Pimenta & Lima (2012). On the paradigms in teacher training and apprenticeship concepts, our discussion is underpinned by Ghedin (2006), Libâneo (2006), Pimenta (2006), and Pimenta & Lima (2006). In the scope of English teacher education, the researches of Burns (2017), Freeman (2002), Freeman, Orzulack & Morrissey (2009), Graves (2009), Gimenez & Furtoso (2008), Johnson (2009a; 2009b), Paiva (2003), Richards (2002), among others, led the discussion around teaching concepts, the knowledge base in second language teacher education, and the English Language program. The studies by Almeida Filho (2005 [1993]), Bandeira (2015), Basso (2001), Bricks (2019), Coelho (2019), Lima (2013), Sant'ana (2007; 2017), Santana (2005), Santana & Ortiz Alvarez (2015), and Souza & Souza (2013; 2015), regarding competencies, also underlay our reflections. As regards the beliefs, we are endorsed by Barcelos (2006a; 2007; 2011; 2015). Perceiving the initial teacher education as a complex adaptive system, we sustain our discussion in Bertalanffy's (2009 [1968]) General Systems Theory, in Larsen-Freeman and Cameron (2008) on Complex Adaptive Systems, and in Borges (2016), whose chaotic model of reflective development of the additional language teacher’s professionalism helped us understand the reorganization of the last two apprenticeship terms. We applied a qualitative approach from an ethnographic perspective, focusing on the participants' experiences. Case study and documentary research were our methodological procedures. The data were constituted from narratives, apprenticeship reports, lesson plans, and daily audio recorded by the nine participants of this research. The results showed that, in the learning-teaching system dynamics, beliefs emerge as their trajectory’s most influencing elements. In the interaction with other systems, such as apprenticeship, school, and teaching, these beliefs expand in the learning-teaching system. Different attractors are evident in the teaching system, especially in the construction of the methodology applied by the participants. Moreover, in the professional identity system, we notice attractors related to the construction of teachers’ knowledge and competences. The data also revealed that the traditional model of supervised apprenticeship, supported by the course pedagogical syllabus, is not ideal for the development of a professional identity that aims at the critical reflection. However, the interaction of the learning-teaching system with other systems favored the participants’ action and brought out possibilities of new paths and initial conditions.